HUBUNGAN OBESITAS DAN SIKLUS MENSTRUASI DENGAN KEJADIAN INFERTILITAS PADA PASANGAN USIA SUBUR DI KLINIK DR.HJ. PUTRI SRI LASMINI SpOG (K) PERIODE JANUARI-JULI TAHUN 2017 - Dewi Susilawati (STIKes MERCUBAKTIJAYA, 2019)
Data on the prevalence of infertility in Indonesia is 10-15% of the 40 million fertile couples who experience fertility problems. Factors affecting infertility are obesity, menstrual cycle disorders, stress, and diet. The purpose of the study was to determine the relationship between obesity and menstrual cycle with the incidence of infertility in the clinic dr. Hj. Putri Sri Lasmini SpOG (K) Period January-July 2017. This type of research is analytical. The place of research was conducted at the clinic dr. Hj. Putri Sri Lasmini SpOG (K) on August 11, 2017. The population in the study were all PUSs diagnosed with infertility in the clinic dr. Hj. Putri Sri Lasmini SpOG (K) as many as 184 people. The study sample was 46% of EFA patients diagnosed with infertility. The type of data used is secondary data. Data is processed through editing, coding, entry, tabulating, and cleaning, by analyzing univariate and bivariate using the chy-square test. The results obtained from 46 respondents who were diagnosed with infertility, 33 respondents (71.7%) recorded obesity, 35 respondents (76.1%) who recorded irregular menstrual cycles, 25 respondents (54.3%) who were diagnosed with primary infertility. There is a relationship between obesity (p. Value = 0.024), menstrual cycle (p. Value = 0.016) with the incidence of infertility. The results of this study concluded that obesity and menstrual cycles have a relationship to the incidence of infertility. It is expected that for EFA to immediately check themselves if they have not received a child after 1 year of marriage. Keywords: Infertility, Obesity, Menstrual Cycle